IMPRESSION CYTOLOGY OF TARSAL CONJUNCTIVA IN LONG-STANDING OCULAR PROSTHESIS WEARERS: CASE REPORTS - Mohd-ali, Bariah; Mohd-saman, Mohd Norhafizun (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Impression cytology is a simple technique that can be used to identify patients who are at risk of developing ocular surface disorders. Giant papillary conjunctivitis (GPC) is an allergic reaction affecting the ocular tarsal conjunctiva predominantly associated with contact lens wear and also observed in anophthalmic patients wearing ocular prosthesis. Here, we described the outcomes of using impression cytology technique in diagnosing GPC in two long-standing ocular prosthesis wearers.